Signal amplification through nucleotide extension and excision on a dendritic DNA platform - Capaldi, Stephen (Oxford University Press, 2000)
Techniques that provide strong signal amplification are useful in diagnostic applications, especially in detecting low concentrations of non-amplifiable target molecules. A versatile and strong signal amplification method based on activities of a DNA polymerase to generate high concentrations of pyrophosphate (PPi) is described. The generation of PPi is catalyzed by nucleotide extension and excision activities of a DNA polymerase on an oligonucleotide cassette. The signal is generated upon enzymatic conversion of PPi to ATP and ATP levels subsequently detected with firefly luciferase. Bioluminesence produced by an oligonucleotide cassette consisting of just two polymerase reaction sites is sufficient to detect them at low attomole levels. The attachment of a large number of these oligonucleotide cassettes to DNA dendrimers enabled the detection of such polyvalent substrate molecules at low zeptomole (10(–21) mol) concentrations. The extent of signal amplification obtained with dendrimer substrates is comparable to exponential target amplifications provided by nucleic acid amplification methods. The attachment of such PPi-generating dendritic DNA platforms to ligands that mediate target recognition would potentially permit detection of extremely low concentrations of analytes in diagnostic assays.